Size Order of the Capitals of the kingdom of Saudi Arabia Regions, An Analytical Study through the Modified Rank-size Rule according to 2022 - Abbakar, Mustafa Mohamed Ali (Journal of Humanities & Social Sciences, 2024)
This research dealt with the issue of cities ranks in the geographical region based on urban characteristics, and accordingly it dealt with the capitals of the kingdom of Saudi Arabia regions, including Riyadh. The research is to reveal the real ranks of the capitals of Saudi Arabian regions according to the different urban influencers. The researcher used the geographical statistical tools, the regional method and the modified rank-size rule. And the tools used included maps, mathematical equations, Excel 2016, Map Distance and earth.google.com. The study concluded that: The theoretical curve is far from the supposed straight-line axis of Zipf rule and that it intersects the actual curve, which means imbalance of ranks between the Saudi Arabian regions capitals. The recommendations were: controlling the increasing expansions in the big size cities, making a population policy to close size ranks and enhance the role of attractive factors in the small size cities.
Keywords: Size Ranks; Capitals Of Regions; Kingdom Of Saudi Arabia; Modified Rank; Size Rule